2020
DOI: 10.3389/fpsyg.2020.566725
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Response Instruction and Target Group on the BIAS Map

Abstract: Response instructions—inviting participants to respond from a certain perspective—can significantly influence the performance and construct validity of psychological measures. Stereotype Content Model (SCM) and then the BIAS map (“behaviors from intergroup affect and stereotypes”) were originally developed as universal measures of shared cultural stereotypes—participants’ perceptions of what most of the people in a society think about the target group—and their related social-structural antecedents, emotions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 86 publications
1
18
0
3
Order By: Relevance
“…I focus here on the Roma, the stigmatized minority of the two groups. In line with Kotzur et al (2020), Findor et al (2020) found that stereotype ratings of the Roma were more positive on both the warmth and competence dimensions in the individual condition. Moreover, they found that the reported levels of contempt and envy toward the Roma were higher, and admiration and pity lower, in the collective condition as compared to the individual condition.…”
Section: Stereotypes and Prejudices As Cultural And Individual-level supporting
confidence: 57%
See 4 more Smart Citations
“…I focus here on the Roma, the stigmatized minority of the two groups. In line with Kotzur et al (2020), Findor et al (2020) found that stereotype ratings of the Roma were more positive on both the warmth and competence dimensions in the individual condition. Moreover, they found that the reported levels of contempt and envy toward the Roma were higher, and admiration and pity lower, in the collective condition as compared to the individual condition.…”
Section: Stereotypes and Prejudices As Cultural And Individual-level supporting
confidence: 57%
“…This individual approach also has a long history in social psychology (Stangor and Schaller, 1996). Until recently (Findor et al, 2020;Kotzur et al, 2020) however, these two approaches to the measurement of the constructs in the SCM had not been systematically compared. As illustrated by the results pertaining to the social perception of asylum seekers/refugees detailed above, varying the instructions may produce results that have diverging substantive interpretations.…”
Section: Stereotypes and Prejudices As Cultural And Individual-level mentioning
confidence: 99%
See 3 more Smart Citations